Penerapan Metode Demonstrasi Guna Meningkatkan Hasil Belajar Siswa Kelas XI IPA pada Pembelajaran Pendidikan Agama Islam di SMA Muhammadiyah 2 Wuluhan - Styawan, Yusril; Rofi, Sofyan; Huda, Hairul (Indonesian Journal Publisher, 2023)
This research aims to determine the improvement in students' learning outcomes through the application of the demonstration method in the subject of Islamic Religious Education, specifically the topic of Funeral Prayer (Shalat Jenazah), in class XI Science at Muhammadiyah 2 Wuluhan High School. The research method used in this study is Classroom Action Research (CAR). The research was conducted from May 10, 2023, to May 25, 2023, in class XI Science at Muhammadiyah 2 Wuluhan High School. Data collection method was a test, and the instrument used was a student test sheet. Based on the research results obtained, student engagement increased during the implementation of the demonstration method. Specifically, the percentage of learning achievement in Cycle I was 77%, and in Cycle II, it increased to 85%. The conclusion drawn from this research is that teaching the demonstration method for the Funeral Prayer material showed that the application of the demonstration learning method led to an increase in students' learning outcomes, with a percentage increase in the pre-cycle, Cycle I, and Cycle II in each meeting, successfully meeting the completion criteria.